Serum CA125 concentration as a predictor of peritoneal dissemination of colorectal cancer in men and women. Issue 47 (November 2016) - Huang, Chi-Jung; Jiang, Jeng-Kai; Chang, Shih-Ching; Lin, Jen-Kou; Yang, Shung-Haur
Abstract : Abstract: Peritoneal dissemination (PD) of cancer is difficult to diagnose. Previous reports have shown that carbohydrate antigen 125 (CA125) is a sensitive marker of PD of gastric cancer. However, CA125 has not been evaluated as a marker of colorectal cancer (CRC), and its accuracy in men is controversial. The aim of this study was to compare the ability of CA125 and carcinoembryonic antigen (CEA) to predict PD of CRC in men and women. Preoperative CA125 and CEA concentrations were measured in 853 people (510 men, 343 women) over 10 years. PD was confirmed intraoperatively in 57 patients. The predictive ability was compared between CA125 and CEA. Compared with CEA, CA125 concentration had a lower sensitivity, higher specificity, and diagnostic accuracy, and significantly greater area under the curve. Further analysis of CA125's sensitivity and specificity among CEA-negative group (n = 514) showed acceptable sensitivity (57.1%) and good specificity (92.0%). In men and women, CA125 concentration did not increase with stage from I to IV unless PD was present ( P  < 0.001). CEA concentration was increased in women with metastasis with PD ( P  < 0.001) or without PD ( P  < 0.001), but was increased only in men with metastasis without PD ( P  < 0.01). CA125 concentration correlated with PD grade for men and women, but CEA concentration correlated with grade only in women. When analyzed according to the primary tumor site, CA125 concentration in men did not differ between patients with the primary site in the right or left colon, or the rectum, regardless of PD status. By contrast, CA125 concentration differed between PD-positive and PD-negative patients with cancer in the right ( P  < 0.001) or left ( P  < 0.001) colon but not in the rectum. CEA concentration in men did not differ according to the primary site or PD status. In women, CA125 and CEA concentrations differed significantly between the PD-positive and PD-negative groups in patients with the primary tumor in the right ( P  < 0.001) or left ( P  < 0.001) colon; tumor sites did not differ between the PD-positive and PD-negative groups. These findings suggest that CA125 is a better tumor marker than CEA for predicting PD of CRC in both men and women.